The role of government towards sea nomads life well-being - Pulpits Sari, Meri Enita; Isa, Khairunesa; Wan Muda, Wan Hanim Nadrah; Ahmad, Abd. Rahman; Ngadiran, Nurizah (Hampstead Psychological Associates, 2020)
The level of community well-being was an indicator used to measure a nation’s development. Similarly, it can be utilised as an indicator for Batam District. Rapid development caused the entire Batam community to experience change, especially socioeconomically where the Sea Nomads community is concerned. Traditional fishing remains as the sole income generation activity for this community, thus proving it difficult for this community to attain a good prosperity level. The objective of this research is to determine the extent of government’s role in shaping the level of prosperity in the lives of the Sea Nomads community. This study, which is conducted through survey using distribution of questionnaires, determined that the role of the government towards the prosperity level of the Sea Nomads community is average. It is suggested that the government investigates the aspect of community needs before conducting various empowerment programmes. Exposure to the latest approach and hands-on skills must also be provided to the community to promote creativity in heightening the prosperity of their lives, especially socially and economically.